THE INFLUENCE OF WORK MOTIVATION, WORK DISCIPLINE AND WORK ENVIRONMENT ON THE PERFORMANCE OF SURABAYA CITY HEALTH OFFICE EMPLOYEES - Istanti, Enny; GS, Achmad Daengs (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Human resource management is part of organizational management that focuses on human resource elements. The purpose of this study is to determine the influence between the variables of work motivation, work discipline and work environment simultaneously on the performance of employees of the Surabaya City Health Office and to determine the influence between the variables of work motivation, work discipline and work environment partially on the performance of employees of the Surabaya City Health Office. The sampling technique in this study is the probability sampling technique, which is a sampling technique that provides equal opportunities for each element (member) of the population to be selected as a member of the sample. From the results of the study, the value of the lowest or weakest work discipline variables in influencing performance. For these unfavorable work discipline conditions, the inherent supervision (waskat) of the leadership needs to be improved again to stimulate employee discipline. Based on descriptive analysis, it can be seen that basically the respondent's assessment of each observed variable is positively assessed by the research respondent.